Transcriptome and proteome revealed the differences in 3 colors of earlobe in Jiangshan Black-bone chicken - Shiru Li; Yu Du; Xue Du; Xiangying Ding; Ayong Zhao; Zhijun Wang (Poultry Science, 2024)
ABSTRACT: The earlobe is a featherless, exposed thickening located beneath the ear canal of chickens, which plays a visual signaling role in age, performance, mental vitality, reproduction, and other aspects. However, despite its importance, there have been few studies on the color differences and formation mechanisms of chicken earlobes, particularly the structurally blue earlobes characteristic of the Jiangshan black-bone chicken. In this study, we explored the physiological mechanisms that may influence the formation of differently colored earlobes using 3 types of earlobes from Jiangshan black-bone chickens: light peacock green (Green group), dark peacock green (Blue group), and dark reddish purple (Black group). All 3 earlobe colors exhibited positive melanin Masson-Fontana staining, and the thickness of collagen fibers in the dermis decreased in the order of Green, Blue, and Black groups. A total of 1,953 differentially expressed genes (DEGs) were detected in the 3 earlobes through mRNA sequencing, among which the GO term “collagen trimer” was significantly enriched in DEGs between groups. Additionally, 716 differentially expressed proteins (DEPs) were identified in the 3 earlobes using 4D-DIA proteomics, with the term “collagen fibril organization” being significantly enriched in DEPs between the Green and Black groups. Integrated analysis of transcriptome and proteome data revealed that 12 DEGs and DEPs were commonly differentially expressed between the Green and Black groups, including the gene LUM (corneal keratan sulfate proteoglycan), which was significantly enriched in the ''collagen fibril organization'' GO term. In conclusion, our study suggests that LUM plays a crucial role in the formation of peacock green earlobes in Jiangshan black-bone chickens. The high level of LUM in peacock green (Green and Blue groups) may affect collagen nanostructures, leading to a stronger effect of melanin-supported dermal collagen on the production of non-iridescent structural colors through coherent scattering, resulting in a bright structural blue color in Jiangshan black-bone chickens. In contrast, the low expression of LUM in dark reddish purple (Black group) reduces the reflection of non-iridescent structural colors, making the earlobe color appear almost black, similar to melanin.